ANALYSIS OF THE INFLUENCE OF GOOD GOVERNANCE FACTORS TO REGIONAL GOVERNMENT PERFORMANCE LANGKAT DISTRICT - Azmal, Erian (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of accountability, transparency, responsiveness, rule of law, efficiency and effectiveness on the performance of Langkat District Administration.The population was all Regional Government Work Units i.e. 104 people.The samples were taken by employing census method in which the whole population was taken as the samples.The hypothesis testing is done by using multiple linear regression testing assisted by SPSS (Statistical Package for Social Science) version 22. The results of this research are simultaneously accountability, transparency, responsiveness, rule of law, efficiency and effectiveness significantly influenced the performance of Langkat District Administration.Partially accountability, transparency, responsiveness, rule of law, efficiency and effectiveness have significant positive influence on the performance of Langkat District Administration.